2019
DOI: 10.5603/fm.a2018.0087
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the styloid process length in a Greek population

Abstract: Background: The styloid process (SP) is a slender cylindrical bony projection of the temporal bone with 2 ligaments and 3 muscles attached to it. Symptomatic SP elongation is also referred to, as Eagle's syndrome. The aim of the present study is to investigate the distribution of the SP length in a young adult Greek population. Materials and methods: Moreover, we provide a comparison of the results by using two different methods for assessing SP elongation, as described in the literature. Finally, we explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 52 publications
4
15
0
9
Order By: Relevance
“…A strong statistical correlation (r= 0.767, p<0.001) was found between the length of the right (29.4 mm) and the left (29.1 mm) styloid processes. Our findings were consistent with other studies published [13,23,29]. Although there is no consensus regarding the presence of elongated styloid process and the affected side, most patients have unilateral complaints [3,[9][10][11][12].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…A strong statistical correlation (r= 0.767, p<0.001) was found between the length of the right (29.4 mm) and the left (29.1 mm) styloid processes. Our findings were consistent with other studies published [13,23,29]. Although there is no consensus regarding the presence of elongated styloid process and the affected side, most patients have unilateral complaints [3,[9][10][11][12].…”
Section: Discussionsupporting
confidence: 93%
“…Previous literature has shown that the concept of normality of the styloid process size is variable. Eagle documented an average length from 25 to 30 mm, but recent reports suggest different cut-off values [1,2,13]. In this study the mean styloid process size in males was 34.6 mm, which is relatively long.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations